2006
DOI: 10.1038/ncb1435
|View full text |Cite
|
Sign up to set email alerts
|

Amplification of CRAC current by STIM1 and CRACM1 (Orai1)

Abstract: Depletion of intracellular calcium stores activates store-operated calcium entry across the plasma membrane in many cells. STIM1, the putative calcium sensor in the endoplasmic reticulum, and the calcium release-activated calcium (CRAC) modulator CRACM1 (also known as Orai1) in the plasma membrane have recently been shown to be essential for controlling the store-operated CRAC current (I CRAC ) [1][2][3][4] . However, individual overexpression of either protein fails to significantly amplify I CRAC . Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

30
421
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 537 publications
(454 citation statements)
references
References 15 publications
30
421
1
2
Order By: Relevance
“…Using elegant screening approaches including positional cloning from the SCID patients, Feske and colleagues [14] have shown that a member of a new class of proteins, called ORAI (keepers of gates of heaven, from Greek mythology), is part of the CRAC channel complex. A similar conclusion was independently reached by others [15][16][17][18], who in addition showed that ORAI1 increased CRAC currents if expressed with the CRAC activator STIM1. STIM1 has been previously shown to mediate CRAC activation after Ca 2+ store depletion [19][20][21][22].…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Using elegant screening approaches including positional cloning from the SCID patients, Feske and colleagues [14] have shown that a member of a new class of proteins, called ORAI (keepers of gates of heaven, from Greek mythology), is part of the CRAC channel complex. A similar conclusion was independently reached by others [15][16][17][18], who in addition showed that ORAI1 increased CRAC currents if expressed with the CRAC activator STIM1. STIM1 has been previously shown to mediate CRAC activation after Ca 2+ store depletion [19][20][21][22].…”
Section: Introductionsupporting
confidence: 81%
“…While the importance of Ca 2+ entry via STIM/ORAI/ CRAC for T cell proliferation, activation and even tolerance is undisputed [10,[13][14][15]23], very little is known about the correlation between T cell activation following formation of the IS and the amplitude and kinetics of the intracellular Ca 2+ concentration. This is surprising given the potential to control the adaptive immune response through changes in free intracellular calcium concentration ([Ca 2+ ] i ) during T cell activation.…”
Section: Introductionmentioning
confidence: 99%
“…First, we compared the fluorescence recovery after photobleaching (FRAP) of STIM1-CFP in unstimulated cells resting on a polylysine surface to that of STIM1-CFP in caps. We studied cells cotransfected with STIM1-CFP and untagged Orai1, because cotransfection of these two proteins is required for increased CRAC channel function (Mercer et al, 2006;Peinelt et al, 2006;Soboloff et al, 2006;Zhang et al, 2006). There was clear recovery of fluorescence from STIM1-CFP in the ER of unstimulated cells resting on polylysine, but little recovery of STIM1-CFP fluorescence when the bleached region was part of a cap structure in stimulated cells (Figure 3, A and C).…”
Section: The Mobility Of Stim1-cfp and Orai1-yfp Decreases In The Capsmentioning
confidence: 99%
“…Orai1 is a four-pass integral membrane protein found in the PM that forms the channel. Overexpression of STIM1 with Orai1 results in very large CRAClike currents in Drosophila cell lines, Jurkat T-cells, RBL cells, and HEK293 cells (Mercer et al, 2006;Peinelt et al, 2006;Soboloff et al, 2006;Zhang et al, 2006). Recent studies have shown that Orai1 forms multimers and that targeted mutations in Orai1 alter the conductance properties of the CRAC channel Vig et al, 2006a;Yeromin et al, 2006;Gwack et al, 2007b).…”
Section: Introductionmentioning
confidence: 99%
“…Orai 1 is a four-transmembranedomain protein. Knockdown of Orai 1 notably decreased SOCE (Peinelt et al 2006;Soboloff et al 2006). Indeed, it is widely accepted that Orai 1 and STIM 1 concertedly determine SOCE in a variety of cells.…”
Section: Introductionmentioning
confidence: 98%